A creativity feedback package for teachers and students of design and technology (in the UK) - Balchin, Tom (Design and Technology Education: An International Journal, 2008)
The UK Design and Technology National Curriculum (2000) is introduced by an ‘importance of design and technology’ statement, which proposes that by studying the subject, students learn to ‘think and intervene creatively’, ‘become creative problem solvers’ and ‘become innovators’. Teachers of the subject in the UK, however, can look in vain for any practical evaluative tools to help them attach importance to students’ creative processes and products, especially in terms of summative assessment. The GCSE (General Certificate of Secondary Education) exam boards’ coursework or teachers’ guides provide no guidance. For example, no mention of ‘creativity’, ‘creative’ or ‘innovation’ can be found in teacher guides issued by the two main UK design and technology exam boards, Edexcel and AQA (Assessments and Qualifications Alliance). It seems as if creativity is an expected by-product of following the UK National Curriculum (NC). As part of a doctoral thesis completed at Goldsmiths College, University of London, a ‘creativity feedback package’ (CFP) was developed to assist both teachers and students to be clear about what creativity is in design and technology, and how it may be rewarded. This paper is a brief synopsis of some of the major findings from this three year research project, carried out with the aim of developing materials which recognise and support creativity for learners at Key Stage 3 (age 12-14).